Cell abundance and diversity of phytoplankton in coastal water of Tioman Island - Mohammad Noor, Normawaty; Harun, Siti Nor Rahaida; Abdul Latif, Asilah Al-Has; Mohammad, Najma Tasnim; Saad, Shahbudin (2012)
Study on the abundance and diversity has been carried out in Tioman Island from 27th to 30th August 2012. Integrated samples were collected at 16 stations around Tioman coastal waters. Results showed that 116 species of phytoplankton were identified and diatom was the dominant genus followed by dinoflagellates. Potential harmful algal bloom (HAB) species identified were Alexandrium sp, P. sigmoides, Dinophysis caudata, Ceratium furca, C. fusus, C. tripos, Noctiluca scintillans, Chaetoceros spp and Skeletonema costatum. The highest abundance of phytoplankton was at station 14 with cell density of 7.8 x 103 cells/L. The value of diversity index (H) and number of phytoplankton taxa for this station were 3.05 and 0.0.49, respectively. Results indicate that Tioman coastal water has high diversity of phytoplankton.